If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12b + -15 = 129 Reorder the terms: -15 + 12b = 129 Solving -15 + 12b = 129 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 12b = 129 + 15 Combine like terms: -15 + 15 = 0 0 + 12b = 129 + 15 12b = 129 + 15 Combine like terms: 129 + 15 = 144 12b = 144 Divide each side by '12'. b = 12 Simplifying b = 12
| 210=l/6 | | 19b=7+5b | | 35x+17=6(5x+3)+5x-1 | | 270+x(10)=350 | | 31+2r=57 | | 0.3(p+4)=2.7 | | -3y+22-15y=0 | | 7=h/61 | | 0=4x^2+17x-15 | | 1/3=s/954 | | -9-b+8b=-2 | | 2.1x+2.6=-5.8 | | 18x+6-12x-12=24 | | 6z+9-7=4z+2z+12 | | 7x=252 | | -2(x-3)+4=-(x+1) | | 11c-14c=12 | | 3/7×=5 | | 3(x+2)+4x=2(x+3)+5x | | 15x=189 | | (x^(r/s))^(s/r) | | 2j-j=20 | | 2x^2-20x-13=0 | | 5x+18-4x=36 | | s=1/3 | | 44=(2x+1)(x+3) | | -(3y+2)-(2y-6)=2 | | x^4-18x^2-8x+21=0 | | 4x+3y=-7+3y | | 4(10+2x)=3x+5(x+8) | | -10+y+3=4y+-13 | | 3=2.5(8+a) |